TINJAUAN HUKUM PERDA SYARIAH KOTA TASIKMALAYA NOMOR 7 TAHUN 2014 DALAM PRESPEKTIF HUKUM TATA NEGARA - ecep (Program Studi Hukum Tata Negara, 2025)
One of the results of public policy in the regions is regional regulations. Of course, the birth of regional regulations is very much in touch with the interests of the regions concerned. Regional regulations that are now quite an issue to be studied are regional regulations that refer to and have nuances of Sharia that have been enacted in various regions. There are at least 22 regions that implement regional regulations that regulate morality issues and the implementation of Islamic sharia in all areas of life. The presence of regional regulations that have nuances of Islamic Sharia such as anti-vice regional regulations, Qishash Criminal Law, reading and writing the Qur'an for prospective brides and grooms, etc. is not only interesting to observe because of the pros and cons, but also the struggle of ideas behind these regional regulations. The approach used in this study is an Empirical Juridical approach. Research based on an inventory of positive law, the discovery of legal principles and the discovery of inconcretto law, which is complemented by empirical observations of the operationalization of law in society. Sharia Regional Regulations that have been widely implemented in the regions to date are recognized as having benefits, including increasing public security and order. What is also important to study is that the increasing sense of security in society needs to be observed and studied further, because this symptom may simply be an effect or reflection of public fear of sharia. If so, then this symptom is not a true reflection of the strengthening of legal and security institutions. This means that what is actually happening is not citizens' legal compliance due to the objective situation that has been created, but rather because of fear of the sharia police who are perceived to be carrying out their duties in the name of religion. This symptom can shift security authority from the police institution to the sharia authority. This is certainly dangerous, because the image and role of security institutions will continue to decline. Keywords: Sharia Bylaws, Empirical Legal Approach, Constitutional Law.